Water-based binder and preparation method thereof

By using water-based binders prepared with raw materials such as carboxymethylcellulose, hydrazide levodopa modified polysiloxane and aqueous polyacrylate, the existing water-based binders are solved, and the problem of low peel strength and difficulty in resisting electrolyte corrosion in lithium-ion batteries is achieved, better peel strength and bonding performance are achieved, and the service life of the battery is extended.

CN119775957AInactive Publication Date: 2025-04-08CYG NEW ENERGY MATERIAL RESEARCH INSTITUTE (GUANGDONG) CO LTD

Patent Information

Application Number
CN202510274326.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the charging and discharging cycle of lithium-ion batteries, the peeling strength of existing water-based binders is low, which makes the active substance easy to fall off and is difficult to resist the corrosion of the electrolyte, resulting in a degradation of bonding performance.

Method used

The raw materials such as carboxymethylcellulose, hydrazide levodopa modified polysiloxane and aqueous polyacrylate were prepared through condensation reaction, esterification reaction and hydrazine dissociation reaction to prepare a catechol group-rich aqueous binder to enhance its peel strength and adhesion properties.

Benefits of technology

It significantly improves the peel strength and bonding performance of water-based adhesives, protects the electrode materials from electrolyte corrosion, reduces interface resistance, extends the cycle life of the battery and improves the cycle performance and rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a water-based binder and a preparation method thereof, and belongs to the technical field of battery binders. Mixing the carboxymethyl cellulose, the hydrazide levodopa modified polysiloxane and the water-based polyacrylate, heating to 50-60 DEG C, reacting for 3-4 hours, adjusting the pH value to 6-7 after the reaction is finished, adding the defoaming agent, and continuously stirring to obtain the water-based adhesive. According to the preparation method provided by the invention, the carboxymethyl cellulose, the hydrazide levodopa modified polysiloxane and the water-based polyacrylate are used as raw materials to synthesize the water-based binder with a three-dimensional network structure, and the water-based binder can be firmly adhered to the current collector to ensure effective electron conduction; the water-based adhesive provided by the invention has excellent peel strength and adhesive property, and can be used for preparing the lithium ion battery foil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery binders, and in particular relates to a water-based binder and a preparation method thereof. Background Art

[0002] As an important component of lithium-ion batteries, the bonding performance between lithium battery aluminum foil and positive electrode materials directly affects the electrochemical performance and safety of the battery. Since components such as active materials and conductive agents are usually powder materials, the main function of the binder is to tightly bond the active material particles, the active material and the conductive agent, and the active material, the conductive agent and the current collector when preparing the electrode slurry, to prevent the active material particles from falling off due to swelling during the battery charging and discharging process, and to reduce the impedance between the current collector and the electrode material.

[0003] Existing binders can be divided into oily binders and water-based binders according to the different dispersion media. The oily binder is mainly polyvinylidene fluoride. When preparing electrode slurry, polyvinylidene fluoride needs to use the highly toxic and expensive organic solvent N-methylpyrrolidone, which increases production costs and environmental burdens. In addition, the drying process of N-methylpyrrolidone is slow, which easily causes polyvinylidene fluoride to be enriched on the electrode surface, increasing the interface resistance. Therefore, most of the binders currently used in lithium-ion batteries use green and environmentally friendly water-based binders. The water-based binder uses deionized water as the dispersion medium for the electrode slurry. Deionized water has the significant advantage of low cost. At the same time, its environmentally friendly characteristics are in line with the current green chemistry and sustainable development concept requirements. While ensuring the performance of lithium-ion batteries, it effectively reduces the environmental risks and cost pressures in the production process.

[0004] In the category of water-based binders, common types mainly include carboxymethyl cellulose, polyacrylic acid, sodium alginate, guar gum, polyvinyl alcohol and polyamide. However, as far as the overall situation of existing water-based binders at this stage is concerned, there are generally some more prominent problems. Specifically, its peel strength is at a relatively low level. During the charge and discharge cycle of lithium-ion batteries, due to this relatively weak bonding performance, the active material in the electrode is very easy to fall off. In addition, the electrolyte of lithium batteries is usually a system composed of lithium salts dissolved in organic solvents, which has strong chemical activity. When the water-based binder comes into contact with it, it is difficult to effectively resist the erosion of the electrolyte due to its own characteristics. The molecular structure of the binder is easily destroyed and the bonding performance is reduced. After the bonding performance decreases, the water-based binder cannot effectively bond the active material particles together, making the active material particles more likely to loosen and fall off during the battery charge and discharge process. The shedding of active substances will further trigger a series of chain reactions. The most critical one is that it will cause the battery capacity retention rate to drop rapidly, seriously affecting the overall electrochemical performance and service life of the lithium-ion battery. This largely limits the wider and more efficient application of water-based binders in related fields.

[0005] Therefore, providing a water-based adhesive with good peel strength is an important problem to be solved in the art. Summary of the invention

[0006] In order to improve the defects of existing binders, the present invention provides a water-based binder and a preparation method thereof and application in lithium battery foil. Specifically, the technical solution adopted by the present invention includes the following contents: One of the purposes of the present invention is to provide a method for preparing a water-based binder, the method comprising the following steps: Carboxymethyl cellulose, hydrazide-modified polysiloxane and water-based polyacrylate are mixed and heated to 50-60° C. for reaction for 3-4 hours. After the reaction is completed, the pH is adjusted to 6-7, a defoamer is added, and stirring is continued to obtain the water-based binder.

[0007] Furthermore, the preparation method of the hydrazide-modified levodopa polysiloxane comprises the following steps: Epoxysilane is dispersed in deionized water, and the pH value is adjusted to 7-8 and then stirred to react to obtain epoxy polysiloxane. Levodopa and epoxy polysiloxane are stirred to react to obtain Levodopa-modified polysiloxane. Levodopa-modified polysiloxane, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and 4-dimethylaminopyridine are stirred to react in an inert gas protection environment to obtain esterified Levodopa-modified polysiloxane. The esterified Levodopa-modified polysiloxane and hydrazine hydrate are stirred to react to obtain the hydrazide-modified Levodopa-modified polysiloxane.

[0008] Furthermore, the epoxysilane is triethoxy(3-epoxypropyloxypropyl)silane or 3-glycidyloxypropyltrimethoxysilane.

[0009] Furthermore, the weight ratio of levodopa to epoxy polysiloxane is 1:0.08-0.12.

[0010] Furthermore, the weight ratio of the levodopa-modified polysiloxane, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and 4-dimethylaminopyridine is 1:0.5-0.7:0.2-0.3.

[0011] Furthermore, the weight ratio of the esterified levodopa-modified polysiloxane to hydrazine hydrate is 1:10-15.

[0012] Furthermore, the inert gas includes nitrogen or argon.

[0013] Furthermore, the preparation method of the waterborne polyacrylate comprises the following steps: Ethyl methacrylate, isooctyl acrylate, methyl heptenone, and glycidyl methacrylate are stirred, and the initiator and emulsifier are heated to 70-80° C. and stirred for reaction for 4-6 hours to obtain the waterborne polyacrylate.

[0014] Furthermore, the weight ratio of ethyl methacrylate, isooctyl acrylate, methyl heptenone, glycidyl methacrylate, initiator and emulsifier is 1:2~3:4~5:2~3:0.08~0.12:0.06~0.1.

[0015] Furthermore, the initiator is ammonium persulfate or potassium persulfate.

[0016] Furthermore, the emulsifier is sodium lauryl sulfate.

[0017] Furthermore, the weight ratio of the carboxymethyl cellulose, the hydrazide-modified levodopa polysiloxane and the waterborne polyacrylate is 1:4-5:3-4:0.1-0.2.

[0018] Furthermore, the defoaming agent is DF-772 or DF-798.

[0019] A second object of the present invention is to provide a water-based adhesive prepared by a method for preparing a water-based adhesive.

[0020] A third object of the present invention is to provide an application of an aqueous binder in lithium battery foil.

[0021] Furthermore, the lithium battery foil contains the aqueous binder prepared by the above method, or contains the above aqueous binder.

[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention first obtains epoxy polysiloxane through condensation reaction, then obtains L-DOPA-modified polysiloxane through ring-opening reaction of epoxy group and amino group, then generates esterified L-DOPA-modified polysiloxane through esterification reaction, and finally the esterified L-DOPA-modified polysiloxane undergoes hydrazinolysis reaction with hydrazine hydrate to obtain hydrazide-modified L-DOPA-modified polysiloxane. The catechol group in L-DOPA can significantly enhance the peel strength and adhesion performance of hydrazide-modified L-DOPA-modified polysiloxane to electrode materials and current collectors.

[0023] (2) The aqueous binder prepared by the present invention is rich in catechol groups, which can be preferentially oxidized on the electrode surface to form a stable solid electrolyte interface film. This film can not only protect the electrode material from electrolyte corrosion, but also reduce the interface resistance, thereby improving the cycle performance and rate performance of the battery.

[0024] (3) The preparation method provided by the present invention uses carboxymethyl cellulose, hydrazide-modified polysiloxane and water-based polyacrylate as raw materials to synthesize a water-based binder with a three-dimensional network structure. The water-based binder can firmly adhere to the current collector to ensure effective electron conduction. At the same time, the ketone group in the side chain of the water-based polyacrylate and the hydrazine group of the hydrazide-modified polysiloxane form a dynamic hydrazone bond through ketone-hydrazine cross-linking, which can achieve bond breaking and recovery when the active material expands in volume. Its self-healing properties can adapt to the volume change of the active material during the charging and discharging process, effectively avoid the powdering and shedding of the electrode slurry, and extend the cycle life of the battery.

[0025] (4) The aqueous adhesive provided by the present invention has excellent peel strength and bonding properties and can be used for the preparation of lithium-ion battery foil. DETAILED DESCRIPTION

[0026] The technical solution of the present invention will be clearly and completely described below through the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0027] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods.

[0028] DF-772 was purchased from Dongguan Defeng Defoamer Co., Ltd.

[0029] DF-798 was purchased from Dongguan Defeng Defoamer Co., Ltd.

[0030] Preparation Example 1: Preparation of hydrazide-modified levodopa polysiloxane, comprising the following steps: 10 parts by weight of triethoxy (3-epoxypropyloxypropyl) silane were dispersed in 100 parts by weight of deionized water, stirred and mixed at a speed of 200 r / min for 15-20 minutes, and then the pH was adjusted to 7-8, and stirred and reacted at a speed of 200 r / min for 24-28 hours. After the reaction, the mixture was filtered and washed, and vacuum dried at 60°C for 12-15 hours to obtain epoxy polysiloxane; 10 parts by weight of levodopa and 0.8 parts by weight of epoxy polysiloxane were dispersed in 100 parts by weight of a mixed solvent (V 无水乙醇 :V 二甲苯 =2:8), stirred at 300r / min for 8h at 23℃ to obtain L-DOPA-modified polysiloxane; 1 part by weight of L-DOPA-modified polysiloxane was dispersed in 15 parts by weight of dichloromethane by 100W power ultrasound for 15min, 0.5 parts by weight of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide was added and stirred at 300r / min for 2h, and then 0.2 parts by weight of 4-dimethylaminopyridine was added and stirred at 300r / min for 30min to obtain a mixed solution, 3 parts by weight of anhydrous ethanol was added to the mixed solution, and stirred at 300r / min for 36h at 25℃ in a nitrogen protection environment, and then esterified L-DOPA-modified polysiloxane was obtained by dialysis filtration; 2 parts by weight of esterified L-DOPA-modified polysiloxane was dispersed in 50 parts by weight of solvent B (V 无水乙醇 :V 二氯甲烷 =1:1), after adding 20 parts by weight of 85% hydrazine hydrate, the temperature was raised to 75°C and stirred at a speed of 300 r / min for 4 hours to obtain hydrazide-modified L-DOPA polysiloxane.

[0031] Preparation Example 2: Preparation of hydrazide-modified levodopa polysiloxane, comprising the following steps: 10 parts by weight of 3-glycidyloxypropyltrimethoxysilane was dispersed in 100 parts by weight of deionized water, stirred and mixed at a speed of 220 r / min for 16 minutes, and then the pH was adjusted to 7.5, stirred and reacted at a speed of 220 r / min for 25 hours, and after the reaction, the mixture was filtered and washed, and vacuum dried at 60°C for 13 hours to obtain epoxy polysiloxane; 10 parts by weight of levodopa and 0.9 parts by weight of epoxy polysiloxane were dispersed in 100 parts by weight of a mixed solvent (V 无水乙醇 :V 二甲苯=2:8), stirred at 320r / min for 9h at 24°C to obtain levodopa-modified polysiloxane; 1 part by weight of levodopa-modified polysiloxane was dispersed in 16 parts by weight of dichloromethane by 110W power ultrasound for 20min, 0.6 parts of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide was added and stirred at 320r / min for activation for 2.3h, 0.22 parts by weight of 4-dimethylaminopyridine was added and stirred at 310r / min for 40min to obtain a mixed solution, 3.5 parts by weight of anhydrous ethanol was added to the mixed solution, stirred at 350r / min for 40h at 23°C in an argon protection environment, and then filtered through dialysis to obtain esterified levodopa-modified polysiloxane; 2 parts by weight of esterified levodopa-modified polysiloxane was dispersed in 50 parts by weight of solvent B (V 无水乙醇 :V 二氯甲烷 =1:1), after adding 22 parts by weight of 85% hydrazine hydrate, the temperature was raised to 80°C and stirred at a speed of 500 r / min for 4.3 h to obtain hydrazide-modified L-DOPA polysiloxane.

[0032] Preparation Example 3: Preparation of hydrazide-modified levodopa polysiloxane, comprising the following steps: 10 parts by weight of 3-glycidyloxypropyltrimethoxysilane were dispersed in 100 parts by weight of deionized water, stirred and mixed at a speed of 270 r / min for 18 minutes, and then the pH was adjusted to 7.5, stirred and reacted at a speed of 270 r / min for 26 hours, and after the reaction, the mixture was filtered and washed, and vacuum dried at 60°C for 14 hours to obtain epoxy polysiloxane; 10 parts by weight of levodopa and 1 part by weight of epoxy polysiloxane were dispersed in 100 parts by weight of a mixed solvent (V 无水乙醇 :V 二甲苯 =2:8), stirred at 350r / min for 11h at 24°C to obtain levodopa-modified polysiloxane; 1 part by weight of levodopa-modified polysiloxane was dispersed in 18 parts by weight of dichloromethane by 140W power ultrasound for 20min, 0.6 parts by weight of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide was added and stirred at 380r / min for activation for 2.7h, 0.28 parts by weight of 4-dimethylaminopyridine was added and stirred at 380r / min for 50min to obtain a mixed solution, 4.5 parts by weight of anhydrous ethanol was added to the mixed solution, stirred at 380r / min for 44h at 24°C in an argon protection environment, and then filtered through dialysis to obtain esterified levodopa-modified polysiloxane; 2 parts by weight of esterified levodopa-modified polysiloxane was dispersed in 50 parts by weight of solvent B (V 无水乙醇 :V二氯甲烷 =1:1), after adding 28 parts by weight of 85% hydrazine hydrate, the temperature was raised to 80°C and stirred at a speed of 500 r / min for 4.8 h to obtain hydrazide-modified L-DOPA polysiloxane.

[0033] Preparation Example 4: Preparation of hydrazide-modified levodopa polysiloxane, comprising the following steps: 10 parts by weight of triethoxy (3-epoxypropyloxypropyl) silane were dispersed in 100 parts by weight of deionized water, stirred and mixed at a speed of 300 r / min for 20 minutes, and then the pH was adjusted to 8, stirred and reacted at a speed of 300 r / min for 28 hours. After the reaction was completed, the mixture was filtered and washed, and vacuum dried at 60°C for 15 hours to obtain epoxy polysiloxane; 10 parts by weight of levodopa and 1.2 parts by weight of epoxy polysiloxane were dispersed in 100 parts by weight of a mixed solvent (V 无水乙醇 :V 二甲苯 =2:8), stirring at 400r / min for 12h in a 25°C environment to obtain levodopa-modified polysiloxane; 1 part by weight of levodopa-modified polysiloxane is dispersed in 20 parts by weight of dichloromethane by 150W power ultrasound for 30min, 0.7 parts by weight of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide is added and stirred at 400r / min for activation for 3h, 0.3 parts by weight of 4-dimethylaminopyridine is added and stirred at 400r / min for 60min to obtain a mixed solution, 5 parts by weight of anhydrous ethanol is added to the mixed solution, and the mixture is stirred at 500r / min for 48h in a nitrogen protection environment at 25°C, and then filtered through dialysis to obtain esterified levodopa-modified polysiloxane; 2 parts by weight of esterified levodopa-modified polysiloxane is dispersed in 50 parts by weight of solvent B (V 无水乙醇 :V 二氯甲烷 =1:1), add 30 parts by weight of 85% hydrazine hydrate, heat to 85°C, stir at a speed of 300-600 r / min for 5 hours to obtain hydrazide-modified polysiloxane.

[0034] Preparation Example 5: Preparation of epoxy polysiloxane, comprising the following steps: 10 parts by weight of triethoxy(3-epoxypropyloxypropyl)silane were dispersed in 100 parts by weight of deionized water, stirred and mixed at a speed of 300 r / min for 20 minutes, and then the pH was adjusted to 8. The mixture was stirred and reacted at a speed of 300 r / min for 28 hours. After the reaction, the mixture was filtered and washed and vacuum dried at 60°C for 15 hours to obtain epoxy polysiloxane.

[0035] Preparation Example 6: Preparation of water-based polyacrylate, comprising the following steps: 10 parts by weight of ethyl methacrylate, 20 parts by weight of isooctyl acrylate, 40 parts by weight of methyl heptenone and 20 parts by weight of glycidyl methacrylate were stirred and mixed at a speed of 200 r / min, and then 0.8 parts by weight of potassium persulfate and 0.6 parts by weight of sodium dodecyl sulfate were added, and the mixture was stirred at a speed of 500 r / min for 20 minutes in an environment of 23°C, and then the temperature was raised to 70°C and stirred at a speed of 200 r / min for 4 hours to obtain water-based polyacrylate.

[0036] Preparation Example 7: Preparation of water-based polyacrylate, comprising the following steps: 10 parts by weight of ethyl methacrylate, 23 parts by weight of isooctyl acrylate, 44 parts by weight of methyl heptenone and 23 parts by weight of glycidyl methacrylate were stirred and mixed at a speed of 230 r / min, and then 0.9 parts by weight of ammonium persulfate and 0.7 parts by weight of sodium dodecyl sulfate were added, and the mixture was stirred at a speed of 600 r / min for 25 minutes in an environment of 24°C, and then the temperature was raised to 75°C and stirred at a speed of 250 r / min for 5 hours to obtain water-based polyacrylate.

[0037] Preparation Example 8: Preparation of water-based polyacrylate, comprising the following steps: 10 parts by weight of ethyl methacrylate, 27 parts by weight of isooctyl acrylate, 45 parts by weight of methyl heptenone and 25 parts by weight of glycidyl methacrylate were stirred and mixed at a speed of 280 r / min, and then 1 part by weight of potassium persulfate and 0.8 part by weight of sodium dodecyl sulfate were added, and the mixture was stirred at a speed of 700 r / min for 25 minutes at 24°C. Then, the temperature was raised to 78°C and stirred at a speed of 280 r / min for 5.5 hours to obtain water-based polyacrylate.

[0038] Preparation Example 9: Preparation of water-based polyacrylate, comprising the following steps: 10 parts by weight of ethyl methacrylate, 30 parts by weight of isooctyl acrylate, 50 parts by weight of methyl heptenone and 30 parts by weight of glycidyl methacrylate were stirred and mixed at a speed of 300 r / min, and then 1.2 parts by weight of ammonium persulfate and 1 part by weight of sodium dodecyl sulfate were added, and the mixture was stirred at a speed of 800 r / min for 30 minutes in an environment of 25°C, and then the temperature was raised to 80°C and stirred at a speed of 300 r / min for 6 hours to obtain water-based polyacrylate.

[0039] Preparation Example 10: Preparation of water-based polyacrylate, comprising the following steps: 10 parts by weight of ethyl methacrylate, 50 parts by weight of isooctyl acrylate and 50 parts by weight of glycidyl methacrylate were stirred and mixed at a speed of 300 r / min, and then 1.2 parts by weight of ammonium persulfate and 1 part by weight of sodium dodecyl sulfate were added, and the mixture was stirred at a speed of 800 r / min for 30 minutes in an environment of 25°C, and then the temperature was raised to 80°C and stirred at a speed of 300 r / min for 6 hours to obtain water-based polyacrylate.

[0040] Example 1: Preparation of a water-based binder, comprising the following steps: Disperse 10 parts by weight of carboxymethyl cellulose in 400 parts by weight of deionized water, add 40 parts by weight of hydrazide-modified polysiloxane prepared in Preparation Example 1 and 30 parts by weight of water-based polyacrylate prepared in Preparation Example 6, stir at 800 r / min for 1 hour at 23°C, then heat to 50°C and stir at 400 r / min for 3 hours, adjust the pH to 6 after the reaction, add DF-772, and continue stirring at 50 r / min for 30 minutes to prepare a water-based binder.

[0041] Embodiment 2: A preparation of a water-based binder comprises the following steps: Disperse 10 parts by weight of carboxymethyl cellulose in 400 parts by weight of deionized water, add 43 parts by weight of hydrazide-modified polysiloxane prepared in Preparation Example 2 and 35 parts by weight of aqueous polyacrylate prepared in Preparation Example 7, stir at 900 r / min for 1.5 h in an environment of 24°C, then heat to 55°C and stir at 450 r / min for 3.4 h. After the reaction, adjust the pH to 6.5, add DF-798, and continue stirring at 70 r / min for 40 min to prepare an aqueous binder.

[0042] Embodiment 3: A preparation of a water-based binder comprises the following steps: Disperse 10 parts by weight of carboxymethyl cellulose in 400 parts by weight of deionized water, add 48 parts by weight of hydrazide-modified polysiloxane prepared in Preparation Example 3 and 35 parts by weight of water-based polyacrylate prepared in Preparation Example 8, stir at 900 r / min for 1.3 h in an environment of 24°C, then heat to 54°C and stir at 450 r / min for 3.8 h. After the reaction, adjust the pH to 6.6, add DF-798, and continue stirring at 80 r / min for 50 min to prepare a water-based binder.

[0043] Example 4: Preparation of a water-based binder, comprising the following steps: Disperse 10 parts by weight of carboxymethyl cellulose in 400 parts by weight of deionized water, add 50 parts by weight of hydrazide-modified polysiloxane prepared in Preparation Example 4 and 40 parts by weight of water-based polyacrylate prepared in Preparation Example 9, stir at 1000 r / min for 2 hours at 25°C, then heat to 60°C and stir at 600 r / min for 4 hours, adjust the pH to 7 after the reaction, add DF-772, and continue stirring at 100 r / min for 60 minutes to prepare a water-based binder.

[0044] Comparative Example 1: Preparation of a water-based binder, comprising the following steps: Disperse 10 parts by weight of carboxymethyl cellulose in 400 parts by weight of deionized water, add 40 parts by weight of the aqueous polyacrylate prepared in Preparation Example 9, stir at 1000 r / min for 2 hours at 25°C, then heat to 60°C and stir at 600 r / min for 4 hours. After the reaction, adjust the pH to 7 and add DF-772, and continue stirring at 100 r / min for 60 minutes to prepare an aqueous binder.

[0045] Comparative Example 2: Preparation of a water-based binder, comprising the following steps: Disperse 10 parts by weight of carboxymethyl cellulose in 400 parts by weight of deionized water, add 50 parts by weight of hydrazide-modified polysiloxane prepared in Preparation Example 4, stir at 1000 r / min for 2 hours at 25°C, then heat to 60°C and stir at 600 r / min for 4 hours, adjust the pH to 7 after the reaction, add DF-772, and continue stirring at 100 r / min for 60 minutes to prepare a water-based binder.

[0046] Comparative Example 3: Preparation of a water-based binder, comprising the following steps: Disperse 10 parts by weight of carboxymethyl cellulose in 400 parts by weight of deionized water, add 10 parts by weight of epoxy polysiloxane prepared in Preparation Example 5, 40 parts by weight of levodopa and 40 parts by weight of water-based polyacrylate prepared in Preparation Example 10, stir at 1000 r / min for 2 hours at 25°C, then heat to 60°C and stir at 600 r / min for 4 hours, adjust the pH to 7 after the reaction, add DF-772, and continue stirring at 100 r / min for 60 minutes to prepare a water-based adhesive.

[0047] Comparative Example 4: Preparation of a water-based binder, comprising the following steps: Disperse 10 parts by weight of carboxymethyl cellulose in 400 parts by weight of deionized water, add 50 parts by weight of hydrazide-modified polysiloxane prepared in Preparation Example 4 and 40 parts by weight of water-based polyacrylate prepared in Preparation Example 10, stir at 1000 r / min for 2 hours at 25°C, then heat to 60°C and stir at 600 r / min for 4 hours, adjust the pH to 7 after the reaction, add DF-772, and continue stirring at 100 r / min for 60 minutes to prepare a water-based binder.

[0048] Application Example 1: Preparation of aluminum foil positive electrode for lithium battery, including the following steps: The solid content of the aqueous binder prepared in Example 1 was adjusted to 20% with deionized water to obtain a binder to be used; 48 parts by weight of lithium iron phosphate, 6 parts by weight of the binder to be used and 6 parts by weight of conductive carbon black SP were dispersed in 88 parts by weight of deionized water, stirred at a speed of 500 r / min for 6 hours, and then ground with a grinder to obtain an electrode slurry; the electrode slurry prepared above was input into the feeding system of the coating machine, smooth aluminum foil was selected as the substrate, the coating speed was 70 m / min, and the drying temperature was 90°C to obtain a lithium battery aluminum foil positive electrode sheet.

[0049] Application Example 2: Preparation of aluminum foil positive electrode for lithium battery, including the following steps: The solid content of the aqueous binder prepared in Example 2 was adjusted to 20% with deionized water to obtain a binder to be used; 48 parts by weight of lithium iron phosphate, 6 parts by weight of the binder to be used and 6 parts by weight of conductive carbon black SP were dispersed in 88 parts by weight of deionized water, stirred at a speed of 500 r / min for 6 hours, and then ground with a grinder to obtain an electrode slurry; the electrode slurry prepared above was input into the feeding system of the coater, and smooth aluminum foil was selected as the substrate. The coating speed was 70 m / min and the drying temperature was 90°C to obtain a lithium battery aluminum foil positive electrode sheet.

[0050] Application Example 3: Preparation of lithium battery aluminum foil positive electrode sheet, including the following steps: The solid content of the aqueous binder prepared in Example 3 was adjusted to 20% with deionized water to obtain a binder to be used; 48 parts by weight of lithium iron phosphate, 6 parts by weight of the binder to be used and 6 parts by weight of conductive carbon black SP were dispersed in 88 parts by weight of deionized water, stirred at a speed of 500 r / min for 6 hours, and then ground with a grinder to obtain an electrode slurry; the electrode slurry prepared above was input into the feeding system of the coating machine, and smooth aluminum foil was selected as the substrate. The coating speed was 70 m / min and the drying temperature was 90°C to obtain a lithium battery aluminum foil positive electrode sheet.

[0051] Application Example 4: Preparation of lithium battery aluminum foil positive electrode sheet, including the following steps: The solid content of the aqueous binder prepared in Example 4 was adjusted to 20% with deionized water to obtain a binder to be used; 48 parts by weight of lithium iron phosphate, 6 parts by weight of the binder to be used and 6 parts by weight of conductive carbon black SP were dispersed in 88 parts by weight of deionized water, stirred at a speed of 500 r / min for 6 hours, and then ground with a grinder to obtain an electrode slurry; the electrode slurry prepared above was input into the feeding system of the coating machine, and smooth aluminum foil was selected as the substrate. The coating speed was 70 m / min and the drying temperature was 90°C to obtain a lithium battery aluminum foil positive electrode sheet.

[0052] Comparative Application Example 1: Preparation of lithium battery aluminum foil positive electrode sheet, including the following steps: The solid content of the aqueous binder prepared in Comparative Example 1 was adjusted to 20% with deionized water to obtain a binder to be used; 48 parts by weight of lithium iron phosphate, 6 parts by weight of the binder to be used and 6 parts by weight of conductive carbon black SP were dispersed in 88 parts by weight of deionized water, stirred at a speed of 500 r / min for 6 hours, and then ground with a grinder to obtain an electrode slurry; the electrode slurry prepared above was input into the feeding system of the coating machine, smooth aluminum foil was selected as the substrate, the coating speed was 70 m / min, and the drying temperature was 90°C to obtain a lithium battery aluminum foil positive electrode sheet.

[0053] Comparative Application Example 2: Preparation of lithium battery aluminum foil positive electrode sheet, including the following steps: The solid content of the aqueous binder prepared in Comparative Example 2 was adjusted to 20% with deionized water to obtain a binder to be used; 48 parts by weight of lithium iron phosphate, 6 parts by weight of the binder to be used and 6 parts by weight of conductive carbon black SP were dispersed in 88 parts by weight of deionized water, stirred at a speed of 500 r / min for 6 hours, and then ground with a grinder to obtain an electrode slurry; the electrode slurry prepared above was input into the feeding system of the coating machine, smooth aluminum foil was selected as the substrate, the coating speed was 70 m / min, and the drying temperature was 90°C to obtain a lithium battery aluminum foil positive electrode sheet.

[0054] Comparative Application Example 3: Preparation of lithium battery aluminum foil positive electrode sheet, including the following steps: The solid content of the aqueous binder prepared in Comparative Example 3 was adjusted to 20% with deionized water to obtain a binder to be used; 48 parts by weight of lithium iron phosphate, 6 parts by weight of the binder to be used and 6 parts by weight of conductive carbon black SP were dispersed in 88 parts by weight of deionized water, stirred at a speed of 500 r / min for 6 hours, and then ground with a grinder to obtain an electrode slurry; the electrode slurry prepared above was input into the feeding system of the coater, smooth aluminum foil was selected as the substrate, the coating speed was 70 m / min, and the drying temperature was 90°C to obtain a lithium battery aluminum foil positive electrode sheet.

[0055] Comparative Application Example 4: Preparation of a lithium battery aluminum foil positive electrode sheet, comprising the following steps: The solid content of the aqueous binder prepared in Comparative Example 4 was adjusted to 20% with deionized water to obtain a binder to be used; 48 parts by weight of lithium iron phosphate, 6 parts by weight of the binder to be used and 6 parts by weight of conductive carbon black SP were dispersed in 88 parts by weight of deionized water, stirred at a speed of 500 r / min for 6 hours, and then ground with a grinder to obtain an electrode slurry; the electrode slurry prepared above was input into the feeding system of the coating machine, smooth aluminum foil was selected as the substrate, the coating speed was 70 m / min, and the drying temperature was 90°C to obtain a lithium battery aluminum foil positive electrode sheet.

[0056] Comparative Application Example 5: Preparation of a lithium battery aluminum foil positive electrode sheet, comprising the following steps: Weigh 48 parts by weight of lithium iron phosphate, 6 parts by weight of polyvinylidene fluoride and 6 parts by weight of conductive carbon black SP into a ball mill, add 240 parts by weight of N-methylpyrrolidone, and mix at a ball mill speed of 400 r / min for 6 hours to obtain an electrode slurry; input the above-prepared electrode slurry into the coating machine feeding system, select smooth aluminum foil as the substrate, the coating speed is 70m / min, and the drying temperature is 90°C to obtain a lithium battery aluminum foil positive electrode sheet.

[0057] Test Example 1: Peel strength and electrolyte wiping resistance The lithium battery aluminum foil positive electrode sheets prepared in corresponding application examples 1 to 4 and comparative application examples 1 to 5 were subjected to peel strength and electrolyte wiping resistance tests. The test results are shown in Table 1.

[0058] Peel strength: first stick the 3M double-sided tape on the stainless steel plate, stick the electrode on the double-sided tape, roll it back and forth three times with a 1kg roller, tear it 180° in the opposite direction by 0.5~1cm, then fix it on the tensile testing machine, stretch and peel to test the tension. The peel strength value is the peel tension / electrode width.

[0059] Electrolyte wiping resistance: Dip a cotton swab in the electrolyte (1mol / LLiPF6, the solvent is EC and DMC with a volume ratio of 1:1), and wipe back and forth on the same position of the carbon-coated aluminum foil. The wiping distance is about 6cm, and one round trip is counted as one time. Record and observe whether there is any leakage from the aluminum foil substrate after 300 wiping experiments.

[0060] Table 1. Performance test results of carbon-coated aluminum foils prepared in Examples 1 to 4 and Comparative Examples 1 to 5

[0061] It can be seen from Table 1 that the carbon-coated aluminum foils prepared in Application Examples 1 to 4 have good peel strength and electrolyte wiping resistance, while the peel strength and electrolyte wiping resistance of the carbon-coated aluminum foils prepared in Comparative Application Examples 1 to 5 are not as good as those in Application Examples 1 to 4.

[0062] Test Example 2: Battery Cycle Performance Test In a glove box filled with argon, the electrodes prepared in Application Examples 1 to 4 and Comparative Application Examples 1 to 5 were used as positive electrodes, the lithium sheets were used as negative electrodes, 1 mol / L LiPF6 (the solvent was EC and DMC in a volume ratio of 1:1) was used as the electrolyte, and Celgard-2325 commercial separator was used to assemble into CR2025 standard button cells.

[0063] The lithium-ion batteries prepared by using the pole pieces prepared in Application Examples 1 to 4 and Comparative Application Examples 1 to 5 were tested for cycle performance at 0.2C, respectively. The positive electrode active material loading was 1.2 mg / cm 2 , the test results are shown in Table 2.

[0064] Table 2. Lithium-ion battery electrochemical cycle performance test

[0065] It can be observed in Table 2 that, compared with lithium-ion batteries prepared with the traditional lithium battery binder polyvinylidene fluoride, the initial discharge specific capacity and capacity retention rate of lithium-ion batteries prepared with the aqueous binder provided by the present invention are significantly improved, indicating that the aqueous binder provided by the present invention can prolong the cycle life of the battery and effectively improve the cycle performance and rate performance of the battery.

[0066] The above-described embodiments provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected.

Claims

1. A method for preparing a water-based binder, characterized in that: The preparation method comprises the following steps: Carboxymethyl cellulose, hydrazide-modified polysiloxane and water-based polyacrylate are mixed and heated to 50-60° C. for reaction for 3-4 hours. After the reaction is completed, the pH is adjusted to 6-7, a defoamer is added, and stirring is continued to obtain the water-based binder.

2. The method for preparing a water-based adhesive according to claim 1, characterized in that: The preparation method of the hydrazide-modified levodopa polysiloxane comprises the following steps: Epoxysilane is dispersed in deionized water, and the pH value is adjusted to 7-8 and then stirred to react to obtain epoxy polysiloxane. Levodopa and epoxy polysiloxane are stirred to react to obtain Levodopa-modified polysiloxane. Levodopa-modified polysiloxane, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and 4-dimethylaminopyridine are stirred to react in an inert gas protection environment to obtain esterified Levodopa-modified polysiloxane. The esterified Levodopa-modified polysiloxane and hydrazine hydrate are stirred to react to obtain the hydrazide-modified Levodopa-modified polysiloxane.

3. The method for preparing a water-based adhesive according to claim 2, characterized in that: The epoxysilane is triethoxy (3-epoxypropyloxypropyl) silane or 3-glycidyloxypropyltrimethoxysilane.

4. The method for preparing a water-based adhesive according to claim 2, characterized in that: The weight ratio of levodopa to epoxy polysiloxane is 1:0.08-0.

12.

5. The method for preparing a water-based adhesive according to claim 2, characterized in that: The weight ratio of the levodopa-modified polysiloxane, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and 4-dimethylaminopyridine is 1:0.5-0.7:0.2-0.

3.

6. The method for preparing a water-based adhesive according to claim 2, characterized in that: The weight ratio of the esterified levodopa modified polysiloxane to hydrazine hydrate is 1:10-15.

7. The method for preparing a water-based adhesive according to claim 1, characterized in that: The preparation method of the waterborne polyacrylate comprises the following steps: Ethyl methacrylate, isooctyl acrylate, methyl heptenone, and glycidyl methacrylate are stirred, and the initiator and emulsifier are heated to 70-80° C. and stirred for reaction for 4-6 hours to obtain the waterborne polyacrylate.

8. The method for preparing a water-based adhesive according to claim 7, characterized in that: The weight ratio of the ethyl methacrylate, isooctyl acrylate, methyl heptenone, glycidyl methacrylate, initiator and emulsifier is 1:2-3:4-5:2-3:0.08-0.12:0.06-0.

1.

9. The method for preparing a water-based adhesive according to claim 1, characterized in that: The weight ratio of the carboxymethyl cellulose, the hydrazide-modified levodopa polysiloxane and the waterborne polyacrylate is 1:4-5:3-4:0.1-0.

2.

10. A water-based adhesive, characterized in that: The aqueous binder is prepared by the method for preparing an aqueous binder according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Fingerprint-resistant coating for chromium-plated part and preparation method of fingerprint-resistant coating

    CN119144200A

  • Polyamino acid adhesive containing dopa

    JP1995238272A

  • Polysiloxane composition, adhesive, method for producing polysiloxane composition, and method for producing adhesive

    US20240191036A1

Cited By

  • Essence composition based on blueberry extract and preparation method thereof

    CN120330008A